Pengembangan Bahan Ajar Aljabar Linear dengan Menggunakan Model Pembelajaran Matematika Knisley - Ria Anggraeni Syafnuri; Netriwati Netriwati; Dona Dinda Pratiwi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This article aimed to find out the development of teaching materials in the form of modules by using Knisley's mathematical learning model on the subject of decent, interesting, and effective linear transformation used in lectures in Linear Algebra. The test subjects in this study were third semester students of Raden Intan Lampung State Islamic University. This research method is Research and Development (R & D) that uses the ADDIE Model (Analysis, Design, Development, Implementation, and Evaluation). The results of the expert assessment are feasible to use with an average score of 3.00 from material experts and 3.08 from media experts. The response of students in small group trials is interesting with an average score of 2.92, whereas in the trial of a large group the criteria are very interesting with an average score of 3.27. The results of the n-gain calculation at the pretest and posttest are 0.70 included in the high effectiveness category. Therefore, it can be concluded that the linear transformation module using Knisley's mathematics learning model is categorized as feasible, interesting, and effective to be used in Linear Algebra lectures